SOSIALISASI DAN PEMANFAATAN LAHAN DESA UNTUK PENANAMAN TANAMAN OBAT KELUARGA (TOGA) SEBAGAI UPAYA PENINGKATAN IMUNITAS MASYARAKAT DI DESA KONDA SATU SULAWESI TENGGARA - Sahidin, Sahidin; Sani, Asrul; Sadimantara, Gusti Ray; Wahyuni; Malik, Fadhliyah; Sadimantara, Fahria Nadiryati; Muliadi, Rahmat; Mustakim; Karimu, Laila Qodriyah (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Indonesia has great potential for traditional medicinal plants which have been used for generations to maintain health. However, the utilization of home yards as productive land for Family Medicinal Plants (TOGA) is not yet optimal in many areas, including Konda Satu Village, South Konawe Regency. In fact, TOGA can be a source of herbal ingredients that function as a preventive and promotive effort to boost the body's immune system. Therefore, the activity of Socialization and Utilization of Village Land for TOGA Planting was carried out in Konda Satu Village. This activity aimed to increase community knowledge about the benefits and cultivation methods of TOGA, while simultaneously optimizing village land that was not yet productive. The implementation was carried out through counseling and direct practice of planting TOGA, such as turmeric, lemongrass, bitter leaf (sambiloto), and galangal on village land. This activity received a positive response and successfully fostered community awareness and self-reliance in utilizing local natural resources for herbal-based health